Lampungnese Connotative Meaning - Redika Cindra Reranta; Elsa Hana Rahma Putri (TEKNOSASTIK, 2023)
A pair of a word can have similar denotative meanings but it does not mean their meaning are identically the same. In a certain tendency, such as emotion, technique, or situation, they are possibly different. So, the meaning can be different. The type of difference is called connotative meaning.  The understanding of connotative meaning is remarkable since choosing inappropriate words leads to ineffective communication. This study examines the connotative meaning of words in Lampungnese, a language that has contact with other languages in a culturally diverse region, Lampung province. By this study, Lampungnese speakers, both native and non-native can choose the word accurately to then effective communication can be achieved. In this study, data were taken from a direct observation of Lampungnese natural interaction among the natives by the researcher. Next, the researcher applied interviews with twenty 50 years old Lampungnese natives to find out the specific tendency of each datum. After that, a natural social experiment is conducted to reach the respond of Lampungnese while listening to the word given so then the finding will be more accurate. From the efforts mentioned, it was found some pairs of words are denotatively the same and connotatively different. As additional information, they exist in various contexts of communication, such as intelligent quality, feeling, situation, politeness, and activities.